Highly Sensitive and Selective Ethanol Sensor Based on ZnO Nanorod on SnO2 Thin Film Fabricated by Spray Pyrolysis - Tharsika, T.; Thanihaichelvan, M.; Haseeb, A. S. M. A.; Akbar, S. A. (Frontiers in Materials, 2019)
This work reports the fabrication of mixed structure of ZnO nanorod on SnO2 thin film via spray pyrolysis followed by thermal annealing and their gas sensing properties. ZnO/SnO2 nanostructures are successfully prepared on a gold interdigitated alumina substrate by spraying varying mixed precursor concentrations of zinc acetate and tin (IV) chloride pentahydrate solutions in ethanol and thermal annealing. The morphology of the nanostructures is controlled by tailoring the Zn:Sn ratio in the precursor solution mixture. Unique ZnO crystals and ZnO nanorods are observed under a field emission scanning electron microscopy (FESEM) when the Zn/Sn ratio in the precursor solution is in between 13:7 to 17:3 after thermal annealing. The fabricated nanostructures are tested for ethanol, methane and hydrogen in air ambient for various gas concentrations ranging from 25 ppm to 400 ppm and the effect of fabrication conditions on the sensitivity and selectivity are studied. Among the nanostructure sensors studied, the film fabricated with molar ratio of Zn/Sn =3:1 shows better sensitivity and selectivity to ethanol due to high sensing surface area of nanorod. The response to 25 ppm ethanol is found to be as high as 50 at an operating temperature of 400ºC.